(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with the peculiarities of development of skills of reading and translating professional text, analyzes the difficulties faced by students while working with professional terminology, substantiates the basic methods of work with professionally-oriented texts.